Effect of path analysis factors on total fertility rate in Iran in 2000 - Z Rahnavard; M Saadaat Hashemi; H Khalkhaali; F Va'ez-zadeh (Tehran University of Medical Sciences, 2002)
Total fertility rate relates to the number of children that a woman bears in the fertility period of her life. Fertility function is one of the most important health and population indicators. This indicator affects social, health, economic and cultural factors. This study is an ecological or correlative one. Factors affecting total fertility rate in Iran in the year 2000 are studied in this paper. The factors include coverage of women with focus on higher education, infant mortality rate (under 1 year), women's occupation rate, urbanity ratio, mean age in the first marriage of women in the age group 15 to 49 years as per the last census in Iran in 2000 in 26 provinces. The direct and indirect effects of these factors on total fertility rate, with emphasis on path analysis have been determined. Data analysis shows that women's occupation rate is the most important factor in decreasing total fertility rate. Higher education of women is also an important element in this regard. Therefore increase in the number of women with university education not only decreases the total fertility but also increases the occupation of women.